Audit committee characteristics and audit fees: evidence from Malaysia / Siti Salwah Jumali - Jumali, Siti Salwah (2012)
This paper examines the relationship between audit committee characteristics and audit fees of 99 companies listed in Bursa Malaysia. The audit committee characteristics examined in this study are independence of members, accounting and financial expertise, size, activity, gender and ethnicity. Data for this study was collected from the annual reports of 99 top Malaysian companies based on market capitalisation in the year 2009. The results revealed that activity measured by the number of meetings held during the year is positively related to audit fees and support previous views that more meetings held by the audit committee increases the audit fees. This study also found that ethnicity which represents the proportion of Malay directors in audit committees also provide positive significant relationship to audit fees. The possible explanation for the significant relationship is that the Malay directors tend to appoint Top-Four auditors and disclose more in the annual report. Other audit committee characteristics (independence, expertise, size and gender) are insignificant to the audit fees. Thus, future study may explore other variables besides those conducted in this study. This study contributes to this research by reporting an analysis of the relationship of activity and ethnicity of audit committee members with the audit fees. The results of this study will be of interest to stakeholders concerned such as audit committee members, managers, regulators, investors as well as auditors.